Designing a Master Program to Cope with the New and Next Normal (VUCA World, Industry 4.0, and Covid 19): a case study - Gembong Baskoro (IPTEK Journal of Proceedings Series, 2020)
It is not surprisingly that the combination of VUCA World and fast development of Industry 4.0 will become the era of new normal for any organization including but not limited to industries. This new normal will become either Threats and or Opportunities for any organization. Whatever it is, organizations should prepare themselves to face this era of new normal, especially to cope with (the unpredictable) uncertainties, such as the pandemic of Covid 19 and maybe other to come, that impact to the existing operation and future opportunities. At the end the uncertainties directly or indirectly will impact to the sustainability of the business. Therefore, this paper presents a strategic initiative, in term collaboration, between academic and professional to design a master program that cope with this new normal. This paper elaborates the concept of developing skills, upskilling and or reskilling, required to be able to handle uncertainties and complexities in the era of new normal. The concept is simply combining strengths of professional and academic and internalized in a tailored master education program. The concept then operationalized in a multi discipline master program as a case study in a top-notch private industry in Indonesia.